Anticipation in Simultaneous Interpretation - Van Besien, Fred (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractAnticipation refers to the simultaneous interpreter's production of a constituent in the target language before the speaker has uttered the corresponding constituent in the source language. It is the result of hypothesizing on the content of the speaker's utterance before it has been finished. In this article, existing material consisting of German-French simultaneous interpretation published by Lederer (1980, 1981) has been analyzed. Anticipation was revealed to be a very frequent strategy, occurring every 85 seconds. The fact that so many verbs were anticipated suggests that anticipation is a language-specific phenomenon. The material also contains cases of structural anticipation, a strategy which enables the interpreter to postpone the moment at which s/he has to produce a verb.